Interrelation of learning model and peer interaction through motivation on achievement - Rody Satriawan; Lalu Muhammad Fauzi; Sri Supiyati; Muhammad Halqi; Malik Ibrahim (Jurnal Elemen, 2023)
Mathematics is often seen as a complex subject by most students. This has caused their achievement and motivation to be low. This study aims to see whether there is a direct or indirect influence from the independent and intervening variables on the dependent variables. This research is quantitative. The population is grade VIII of one of state junior high school, and the sample is class 8-B which consists of 28 students. The instruments used in data collection were questionnaires and tests. Data were analyzed using path analysis with the help of the Amos 25.0 program. The research result is that the P-value is 0.17<0.05. There is a direct effect of the learning approach on motivation; the P-value is 0.049<0.05. Peer interaction immediately affects achievement; the P-value is 0.035<0.05. There is a direct effect of the learning models on achievement; the P-value is 0.088>0.05. There is no direct effect of peer interaction on achievement; the P-value of 0.023<0.05 has a direct impact on motivation on achievement, the P-value of 0.444>0.05 motivation cannot mediate peer interaction on achievement, and a P-value of 0.024<0.05 with the conclusion that there is an indirect effect between learning model on achievement through motivation.